Nonlinear wave dispersion in the particle method for incompressible fluid - Nekrasova, T.I.; Frank, A.M. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2010)
In the framework of the particle method for incompressible fluid, a dispersion relation for linear surface waves is obtained. The influence of the spatial resolution on the dispersive properties of the method is studied. A comparison with some other numerical methods for free surface flows is performed from the standpoint of accuracy of wave dispersion simulation.